Snow Loads : 2024 IBC and ASCE/SEI 7-22 - Fanella, David A. (McGraw-Hill's AccessEngineering., 2023)
This Excel workbook determines snow loads in accordance with the 2024 IBC and ASCE/SEI 7-22. Balanced and unbalanced roof loads are calculated in Imperial and metric units for the following: (1) monoslope, hip, and gable roofs, (2) curved roofs, and (3) sawtooth roofs. Drift snow loads are calculated on (1) lower roofs of attached and adjacent structures, (2) parapet walls, and (3) roof projections. Sliding snow loads are calculated on lower roofs of attached and adjacent structures.